Peningkatan Pemecahan Masalah Matematika Materi Pythagoras Melalui Penerapan Problem Based Learning(Ptk Siswa Kelas Viii Semester Gasal Smp Kasatriyan 1 Surakarta Tahun 2016/2017) - Shalihah, Wakhidah Nur; Dra. Sri Sutarni, M.Pd (2017)
ABSTRACT The background of this study weak of Problem solving Pythagoras math class VIII students of SMP Kasatriyan 1 Surakarta C. The purpose of this study to describe inprovement of SMP Kasatriyan 1 Surakarta student is solving math problem with Pythagoras by using Problem Based Learning. This study belongs to action class research. The technique of collecting data are observation, testing, field notes, and documentation. The results showed that the improvement of SMP Kasatriyan 1 Surakarta student in solving math problem with Pythagoras can be seen from: 1. Showing understanding the problem Pythagorasfrom before 5 students (22,73%) and afterthe action increase become 14 students (63,64%) 2. Choose this breaking problem methods Pythagoras as correct from before 3 students (13,64%) and after the action increase become 13 students (59,09%) 3. Finishing problem Pythagoras principle from before 4 students (18,18%) and after the action become 13 students (59,09%). Based on the dta above can be concluded that the applying of Problem become Based Learning can be improve math problem Pythagoras. Keywords: Problem solving, Pythagoras, Problem Based Learning